2018
DOI: 10.3390/genes9030156
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the PYL Gene Family and Identification of PYL Genes That Respond to Abiotic Stress in Brassica napus

Abstract: Abscisic acid (ABA) is an endogenous phytohormone that plays important roles in the regulation of plant growth, development, and stress responses. The pyrabactin resistance 1-like (PYR/PYL) protein is a core regulatory component of ABA signaling networks in plants. However, no details regarding this family in Brassica napus are available. Here, 46 PYLs were identified in the B. napus genome. Based on phylogenetic analysis, BnPYR1 and BnPYL1-3 belong to subfamily I, BnPYL7-10 belong to subfamily II, and BnPYL4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 51 publications
5
48
0
Order By: Relevance
“…The members of a gene family, having significant similarities in both structure and function, encode similar protein products. However, they are usually located at different positions on the same chromosome or on different chromosomes, each with different regulatory patterns and functions 39 . In our previous study, the two members of the BoaPDS gene family in Chinese kale (BaPDS1 and BaPDS2) played different and indispensable roles, and their functions were partially complementary 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The members of a gene family, having significant similarities in both structure and function, encode similar protein products. However, they are usually located at different positions on the same chromosome or on different chromosomes, each with different regulatory patterns and functions 39 . In our previous study, the two members of the BoaPDS gene family in Chinese kale (BaPDS1 and BaPDS2) played different and indispensable roles, and their functions were partially complementary 20 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, their expression profiles in various tissues have been revealed substantial differences among PYL genes for many plants. For example, some PYLs respectively displayed relatively higher levels in seeds of soybean, the callus of B. rapa , and the latex of rubber tree than other tissues [ 23 , 24 , 40 , 41 ]. Moreover, most OsPYLs were expressed in all organs of rice, OsPYL3 and OsPYL5 were predominantly expressed in leaves, and OsPYL1 in roots [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these miRNAs identified have been implicated in stress responsiveness and development (Additional file 8). In an earlier study with Brassica napus, 26 miRNAs targeting 11 BnPYL genes were identified, and predicted that 10 members of miR169 target BnPYL1-4 [85]. For better understanding, each OsPYL gene targeted by different miRNAs is depicted by different colour and shape (Fig.…”
Section: Regulation Of Gene Expressionmentioning
confidence: 99%